Impact of transaction costs on supply operations and price competitiveness in wholesale marketing: a study in reference to Mexico. Issue 4 (22nd August 2019) - ,; Rajagopal, Ananya
Transaction costs make significant impact on determining the costs of logistics and inventory in companies marketing consumer wholesale products. Effective management of transaction cost helps companies ensure competitive prices, and induce loyalty among the consumers. This paper aims at analysing the transactions cost, and its relationship with wholesale prices. It critically examines the previous studies on transaction cost approach of wholesaler firms in reference to the cost incurred in their brands using 'direct-to-customer' strategy. Data in this study has been collected in reference to two large wholesale outlets in Mexico City. This study reveals that wholesaler brands are price competitive and effectively reduce the uncertainty of supplies as they address the existing demand in the market. The wholesale brands largely meet the price expectation of consumers and enhance their satisfaction level. Large wholesaling firms reduce their transaction costs by lowering the margin spread among the suppliers, and obtaining supplies from a limited number of suppliers nationwide.